POLITICAL ETHICS IN BERGER DIALECTICS AGAINST THE MEANING OF POWER OF THE SOUTH NIAS DPRD MEMBERS FOR THE 2014-2019 PERIOD - Manao, Hadirat (UNIVERSITAS PAKUAN, 2021)
The establishment of South Nias Regency is of course accompanied by the formation of new legislatif and executive institutions to run the government. The formation of these institutions provided an opportunity for the emergence of local Nias Selatan elites to take up positions as legislators and regional heads. Reflecting from the above view, this research is a case study that focuses on developing in-depth descriptions and explanations of the meaning of the position of legislatif members in South Nias in 2014. specifically the perspective of Peter L Berger's social construction.At a practical level, this study can be a